Sustaining high-value salmonid populations in regulated rivers : Insights from individual-based modelling of brown trout and Atlantic salmon - Hajiesmaeili, Mahboobeh; Addo, Louis; Watz, Johan; Norrgård, Johnny; Railsback, Steven F.; Syrjänen, Jukka; Blixt, Marco; Piccolo, John (Global Ecology and Conservation, 2024)
To combat climate change, societal pressure to develop fossil-free hydroelectricity is growing. There is a great need, however, for environmental assessment tools that can predict the effects of streamflow regulation on biodiversity in hydropower-regulated rivers. Ecological modelling lets practitioners: 1) set broad bounds on population-level responses of key species and 2) identify knowledge gaps and prioritize research needs. Individual-based models (IBMs) are powerful tools for assessing relative benefits of alternative management actions, and therefore help to develop more sustainable hydropower solutions. We applied the inSALMO 7.3-SD IBM for populations of brown trout (Salmo trutta) and Atlantic salmon (S. salar) in the lower Gullspång River, Sweden. We simulated the effects of various minimum hydropeaking flow releases (from 9 to 21 m3/s) on outmigration production. We found that the number of age-1 outmigrants of both species decreased with increasing minimum flow release of the hydropeaking scenarios. The number of age-2 trout outmigrants did not change considerably with increasing the minimum release, but decreased sharply at the highest flow. The most age-2 salmon outmigrants were produced by flow scenarios with minimum releases of 15 and 18 m3/s. The model predicts, therefore, varying species- and life stage-specific effects of flow regulation. Moreover, increased flow caused juveniles to stay in the river longer and outmigrate at larger size, which exposes them to simulated predation longer but could increase post-outmigration survival. By providing insights into mechanisms driving population dynamics, IBMs can help promote the sustainability of high-conservation-value fish species.